Sulbactam pivoxil powder attributes and compatibility study with excipients - Loreana C. Gallo; Noelia L. Gonzalez Vidal; Fabio F. Ferreira; María V. Ramírez-Rigo (SpringerOpen, 2021)
Abstract Background Sulbactam pivoxil is an irreversible β-lactamase inhibitor that can be used with β-lactam antibiotics to improve antibacterial therapy by the oral route. Relevant properties of this drug for pharmaceutical manufacturing are not available in the open literature. In this work, a solid-state characterization of sulbactam pivoxil at the molecular, particle, and bulk levels was performed. Results Particles exhibited a mean diameter of about 350 μm, irregular shape crystals, and good flow properties. This work presents for the first time the crystal structure of this β-lactamase inhibitor obtained by X-ray diffraction analysis. Fourier-transform infrared results showed the characteristic bands of aliphatic hydrocarbons and ester groups. The differential scanning calorimetry curve exhibited a sharp endothermic peak at 109 °C corresponding to sulbactam pivoxil melting. The thermogravimetric curve revealed a mass loss at 184 °C associated with a decomposition process. This powder showed a moisture content of 0.34% and a water activity of 0.463. Potential interactions between sulbactam pivoxil and common pharmaceutical excipients were evaluated by thermal analysis. The endothermic peak and the enthalpies of melting were preserved in almost all the analyzed mixtures. Conclusion The powder was constituted by micro-sized crystals of sulbactam pivoxil that had suitable physicochemical properties for processing in controlled humidity environments. Thermal analyses suggested that sulbactam pivoxil is compatible with most of the evaluated excipients. The information obtained in the present study is relevant for the development, manufacturing, and storage of formulations that include sulbactam pivoxil.